Designing meaningful interpretive exhibits at ecotourism sites to influence behaviour intention - Mokhli, Nuraain; M., Manohar; Lim, E. A. L. (Malaysian Forester, 2023)
Interpretive exhibits are widely used to convey conservation messages and promote sustainable recreation activities in the forests through interpretive content and design of the exhibits. However, literature hardly indicates the effectiveness of the contents and design utilised in exhibits to deliver such messages to visitors. Research has primarily focused on the effect of interpretive exhibits in enhancing visitors knowledge and experience during the visit rather than the effect of the exhibits design and contents on visitors affective and psychological aspects. The present study evaluates the effectiveness of the interpretive exhibit in influencing university students intention to participate in birdwatching. A quasi-experimental research design was employed to compare the effectiveness of non-interpretive (control group) and interpretive exhibits (intervention group) in influencing students intention to participate in birdwatching. The interpretive exhibit was designed based on students salient beliefs and affect elicited during the interview. Data was collected using a questionnaire from 119 university students. Findings showed that the interpretive exhibit had a significant influence on students birdwatching intention compared to the non-interpretive exhibit. The interpretive exhibit also had a significant influence on students affective responses toward birds and birdwatching. Besides, results from the regression test showed a significant relationship between students affective responses and their intention to participate in birdwatching. Thus, interpretive elements incorporated in the new interpretive exhibit design contributed to the success of influencing students intention to participate in birdwatching.